KADAR LEMAK ES KRIM TEPUNG DAUN KELOR (Moringa oleifera) BERDASARKAN VARIASI VOLUME SARI KACANG TANAH (Arhacis hypogea) - Stella Faubun; H Sinay (Program Studi Pendidikan Biologi FKIP Unpatti, 2017)
Background: Moringa leaves are rich in nutrients and are a source of antioxidants, but are underutilized by the public as a food ingredient because they smell ‘unpleasant '. In an effort to increase the benefits to extend the shelf life of the product and also attract the interest of the community to consume Moringa leaves, Moringa leaves can be processed into flour, then made ice cream with the addition of peanut juice. Method: Implementation of this research was conducted at the Pattimura University Basic Biology Laboratory. This study uses a Completely Randomized Design (CRD). Data from the research results were analyzed using inferential statistics One Way Anova (ANOVA). Results: There was an effect of adding variations of peanut juice (Arachis hypogea) to fat content in Moringa oleifera leaf ice cream ie control of 4,457%, addition of 50 ml peanut juice as much as 5,207%, addition of 75 ml peanut juice as much as 5,956% and the addition of 100 ml peanut juice, fat content of 5.993%. Conclusion: There is an effect of adding variations in peanut juice (Arachis hypogea) to fat content in Moringa oleifera leaf ice cream.